Can Work-Life Balance Mediates the Effect of Workload on Performance? A Study of J&T Express Couriers in DC Sumber Cirebon - Nuriman, Nuriman; Hartati, Wiwi; Risdianto, Risdianto (Strata International Journal of Social Issues, 2025)
This study examines the mediating role of work-life balance (WLB) in the relationship between workload and employee performance among couriers at J&T Express Sumber Cirebon Distribution Center. Using a quantitative approach, we collected data from 62 couriers through validated Likert-scale questionnaires measuring workload (time pressure, mental effort, physical demands), WLB (schedule flexibility, family support), and performance (productivity, reliability). Results from multiple regression analysis reveal that workload negatively impacts performance (β = -0.980, p < 0.001) due to physical/mental fatigue, yet paradoxically enhances WLB (β = 0.574, p < 0.001) through workplace flexibility. WLB partially mediates this relationship (Sobel Z = 2.014), improving performance (β = 0.284, p = 0.029) and explaining 45.9% of variance. These findings extend Job Demands-Resources theory by demonstrating WLB's dual role as both an outcome of workload and a buffer against its performance costs in high-pressure logistics environments. The study offers practical recommendations including dynamic shift scheduling and temporary staffing during peak periods, while suggesting future research explore additional mediators across broader logistics contexts.